Comparison of water level measurement performance for two different types of diaphragm using fiber bragg grating based optical sensors - Ameen, Odai Falah (Penerbit UTM Press, 2016)
A sensor head incorporating a diaphragm was designed and fabricated for water level measurement. It operates in the range of 0-70 cm column height, equivalent to a pressure in atmospheric pressure of 0-6. 86 kPa. The fiber Bragg grating (FBG) was attached on the two types of diaphragm to detect the change in the hydrostatic pressure caused by water at different levels. The diaphragms performance by comparing the sensitivity in within the mentioned range. Optical spectrum analyzer (OSA) was used to record the shift in the Bragg wavelength λB at different water level. The sensitivity of water level measurement using a silicone rubber diaphragm found to be 9.81 pm/cm for 70 cm in water level, while the sensitivity for polymer plastic diaphragm found to be 2 pm/cm at the same level